High-entropy metal oxide and preparation method and application thereof
High entropy metal oxides are prepared through low-temperature calcination, combined with halogenated peroxide nanoenzymes and hydrogen peroxide generation, and solved the environmental protection, cost and equipment requirements in marine biological pollution prevention and control, achieving efficient and environmentally friendly anti-fouling effect , and exhibits excellent performance in the field of photocatalytics.
Patent Information
- Application Number
- CN202411416044.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-10
AI Technical Summary
The prior art has problems in preventing marine biological pollution, high extraction costs, easy degradation and high calcination temperature. The calcination process of high-entropy metal nano-oxide materials has high requirements for equipment and is not suitable for large-scale Production.
Mixing a variety of metal salts with template agents to form a homogeneous sol, and preparing high-entropy metal oxides through aging, drying and low-temperature calcination, combining the application of halogenated peroxide nanoenzymes to prevent pollution and prepare strong hydrogen peroxide oxidizers to form environmental protection , durable anti-fouling material.
It has achieved high specific surface area and can regulate local electronic structures, with excellent catalytic performance and anti-marine biological pollution performance, is suitable for large-scale production, and has significant advantages in the field of photocatalysis, environmentally friendly and non-toxic. Low cost.
Smart Images

Figure CN119284954A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of marine metal materials, and in particular, relates to a high entropy metal oxide and a preparation method and application thereof. Background Art
[0002] The problem of marine biofouling is becoming increasingly serious. There are a large number of microorganisms, bacteria and other marine plants and animals growing unhealthily on the underwater surface in the ocean, which has widely affected the sustainable development of marine economic activities. In order to prevent marine biofouling, many methods were initially adopted, such as applying toxic chemicals (such as asphalt, tar and substances containing elements such as copper, arsenic, sulfur, mercury, etc.) on the surface of the hull, and using tributyltin (TBT). However, resisting marine biofouling by releasing toxic substances may induce bacterial resistance. In addition, its release rate is difficult to control, which may cause the antifouling ability of the coating to decrease over time, and the non-selective lethal toxicity has serious ecological impacts on non-target species, threatening the safety of the marine environment. Therefore, there is an urgent need to seek more environmentally friendly and effective methods to prevent marine biofouling and develop new environmentally friendly and durable antifouling materials.
[0003] Some algae in the ocean have evolved natural anti-fouling properties. The haloperoxidases they secrete can catalyze the conversion of halogen ions in seawater into hypohalous acid with anti-fouling effects, thereby achieving the purpose of preventing biofouling. However, the use of natural enzymes has problems such as high extraction cost, easy degradation, and harsh reaction conditions.
[0004] Recently, researchers have synthesized metal nanomaterials such as V2O5, CeO2 and CrC3N4 with haloperoxidase-like activity by simulating the biomimetic mechanism of biofouling, namely biomimetic enzyme catalysis, and converted H2O2 into HOBr or halogenated metabolites with bactericidal activity. This process simulates the natural defense system, effectively preventing bacterial attachment or biofilm formation, and has the advantages of strong antifouling performance, high stability and low cost. However, traditional nanozymes still face problems such as uneven elemental composition, low active site density and complex catalytic mechanism.
[0005] High entropy metal nanoparticle materials, due to their unique surface atomic configuration and unique d-orbital coupling characteristics of different metal components, enhance the adsorption of oxygen intermediates in the catalytic process and show excellent substrate affinity and catalytic efficiency. Their high specific surface area and tunable local electronic structure make them show dual application potential in marine antifouling and photocatalytic generation of hydrogen peroxide. These materials can form a protective film on the underwater surface through their multi-element synergistic effect and excellent catalytic performance to prevent the attachment and growth of microorganisms, bacteria and other marine plants and animals. At the same time, the in-situ generated hydrogen peroxide strong oxidant can effectively inhibit the formation of biofilm, thus providing an environmentally friendly antifouling strategy. Studies have shown that multi-element high entropy materials have better catalytic performance than single-element materials. For example, Chinese patent CN116037149A discloses a high specific surface area high entropy oxide catalyst, which is a hexavalent spinel high entropy oxide composed of equimolar ratios of the oxides of the hexavalent metals Me, Co, Ni, Cr, Fe, and Mn. The calcination temperature of its synthesis process is 700℃~1000℃, which is used to catalyze the production of p-chlorobenzaldehyde. However, its calcination temperature is too high, and the equipment requirements are high, which is not suitable for large-scale production.
[0006] In addition, high-entropy metal nanooxide materials have the advantages of good size and shape, selectivity and catalytic regeneration, and can also be used in biosensing and antibacterial fields. However, there have been no reports on new high-entropy metal nanoparticle oxide materials and their applications in marine biofouling. Summary of the invention
[0007] In view of the deficiencies in the prior art and actual needs, the present invention provides a high entropy metal oxide and a preparation method and application thereof, which organically combines the application of halogenated peroxide nanozymes for antifouling and the preparation of hydrogen peroxide strong oxidant, contributing new ideas for the sustainable development of the marine economy.
[0008] To achieve the above object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a method for preparing a high entropy metal oxide, the method comprising the steps of adding a plurality of metal salts to a solvent containing a template and mixing them into a uniform sol, and sequentially aging, drying and calcining the sol to obtain the high entropy metal oxide;
[0010] The metal salt is selected from at least five of cerium salts, zirconium salts, hafnium salts, tantalum salts, niobium salts, titanium salts, vanadium salts, molybdenum salts, tungsten salts, copper salts, zinc salts and aluminum salts;
[0011] The template agent is selected from one of polyether P123, branched polyethyleneimine (BPEI), xanthan gum, ε-polylysine, pluronic F-127 and polyvinyl pyrrolidone (PVP).
[0012] In one or more embodiments, the cerium salt is selected from one of cerium oxalate, cerium chloride, cerium nitrate, ammonium cerium nitrate, cerium trifluoromethanesulfonate and cerium stearate; the zirconium salt is selected from one of zirconium acetylacetonate, zirconium oxychloride, zirconium chloride and zirconium nitrate; the hafnium salt is selected from one of hafnium tetrachloride, hafnium n-butoxide and hafnium oxychloride hydrate; the tantalum salt is selected from one of tantalum chloride, tantalum ethoxide, tantalum tetraethanol acetylacetonate and tantalum isopropoxide; the niobium salt is selected from one of niobium pentachloride, ammonium hexafluoroniobate and niobium n-butoxide; the titanium salt is selected from one of titanium tetrachloride, hexafluoro One of titanic acid and titanium acetylacetonate; the vanadium salt is selected from one of vanadium trichloride, vanadium acetylacetonate and ammonium metavanadate; the molybdenum salt is selected from one of molybdenum chloride, ammonium molybdate and molybdenum acetylacetonate; the tungsten salt is selected from one of ammonium tungstate, tungsten hexachloride and tungsten isopropoxide; the copper salt is selected from one of copper nitrate, copper oxalate, copper stearate, copper methanesulfonate and copper chloride; the zinc salt is selected from one of zinc chloride, zinc stearate, zinc oxalate and zinc nitrate; the aluminum salt is selected from one of aluminum nitrate, aluminum acetate, aluminum stearate, aluminum acetylacetonate and aluminum chloride.
[0013] In one or more embodiments, the molar mass of the plurality of metal salts is 0.5 mmol to 10 mol; and the molar mass of the template is 25 to 40 mmol.
[0014] In one or more embodiments, the aging step is: stirring the homogeneous sol for 1 to 2 hours, and then aging it for 40 to 50 hours at a temperature of 35 to 45° C. and a humidity of 45 to 55%.
[0015] In one or more embodiments, the drying temperature is 90 to 110° C., and the drying time is 20 to 30 hours.
[0016] In one or more embodiments, the calcination step is: heating the dried product to 300° C. to 400° C. at a heating rate of 1° C. per minute in air, and then calcining for 3 to 5 hours.
[0017] In one or more embodiments, the metal salt includes 5 mmol cerium nitrate, 2 mmol zirconium oxychloride, 1.5 mmol niobium chloride, 1 mmol tantalum chloride and 0.5 mol hafnium chloride; the template is 35 mmol polyether P123; the obtained high entropy metal oxide is Ce 0.5 Zr 0.2 Nb 0.15 Ta 0.1 Hf 0.05 O x , where X=1-3.
[0018] In one or more embodiments, the metal salt includes 5 mmol cerium nitrate, 2 mmol copper nitrate, 1 mmol zinc nitrate, 0.5 mmol zirconium oxychloride and 0.5 mmol aluminum nitrate; the template is 30 mmol pluronic F-127; the obtained high entropy metal oxide is Ce 0.5 Cu 0.2 Zn 0.1 Zr 0.05 Al 0.05 O x , where X=1-3.
[0019] In one or more embodiments, the metal salt includes 4 mmol copper nitrate, 2 mmol molybdenum chloride, 2 mmol ammonium metavanadate, 1 mmol tungsten hexachloride, 0.5 mmol aluminum chloride and 0.5 mmol titanium chloride; the template is 40 mmol polyvinyl pyrrolidone (PVP); the obtained high entropy metal oxide is Cu 0.4 Mo 0.2 V 0.2 W 0.1 Al 0.05 Ti 0.05 O x , where X=1-3.
[0020] In a second aspect, the present invention provides the application of the high entropy oxide obtained by the above preparation method in the field of marine engineering.
[0021] In one or more embodiments, the application is to use the high entropy oxide for preparing anti-marine biofouling materials.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) The high entropy metal oxide prepared by the method of the present invention not only has a uniform morphology, but also has a composition of multiple elements so that it has a higher specific surface area and a controllable local electronic structure, thereby having better catalytic performance; and it can effectively catalyze the oxidation of halogen ions in the presence of H2O2 oxidant, thereby generating hypohalous acid with strong antibacterial activity, thereby preventing the attachment of marine organisms. Therefore, the high entropy metal oxide of the present invention exhibits excellent anti-marine biofouling performance and has obvious advantages in the field of preparing anti-marine biofouling materials.
[0024] (2) Compared with existing antifouling technologies, the high entropy metal oxide of the present invention will not release heavy metal ions into the ocean during use, which can avoid damage to the marine ecosystem. It has the advantages of being environmentally friendly, non-toxic, low cost, and easy to prepare. It is an ideal environmentally friendly marine antifouling material. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is a scanning electron microscope (SEM) image of the high entropy metal oxide prepared in Example 1;
[0026] Figure 2 is the X-ray diffraction (XRD) pattern of the high entropy metal oxide prepared in Example 1;
[0027] Figure 3 is a UV-visible absorption curve of the bromination process of phenol red catalyzed by the high entropy metal oxide prepared in Example 1;
[0028] Figure 4 is a UV-visible absorption curve of the bromination process of phenol red catalyzed by the high entropy metal oxide prepared in Example 2;
[0029] Figure 5 is a graph of hydrogen peroxide yield of the high entropy metal oxide prepared in Example 1;
[0030] Figure 6 is a graph of hydrogen peroxide yield of the high entropy metal oxide prepared in Example 2;
[0031] Figure 7 This is a photo of the high entropy metal oxide prepared in Example 1 hanging on a board in a real marine environment for 90 days;
[0032] Figure 8 This is a photo of the high entropy metal oxide prepared in Example 2 hanging on a board in a real marine environment for 90 days;
[0033] Fig. 9 This is a photo of the high entropy metal oxide prepared in Example 3 hanging on a board in a real marine environment for 90 days. DETAILED DESCRIPTION
[0034] High entropy alloy (HEAs) is a new alloy system with multiple elements as the main components. MHTsai (MHTsai et al, Materials Research Letters, 2014, 2:107-123) summarized the four typical effects of high entropy alloys, namely the high entropy effect in thermodynamics, the lattice distortion effect in structure, the hysteresis diffusion effect in kinetics and the cocktail effect in performance. These four effects have a significant impact on the organization and properties of high entropy alloys, making them widely studied and developed in many fields such as hydrogen storage materials, soft magnetic materials, and structural materials. However, no new high entropy metal oxide materials and their applications in marine biofouling have been found so far.
[0035] Since high entropy metal oxide materials have the advantages of good size and shape, selectivity and catalytic regeneration, they have been widely studied in many fields. However, there is a common problem in this field, that is, the calcination process of high entropy metal oxide materials requires relatively high temperature. For example, the calcination of most existing high entropy oxide materials requires 700-1000°C or even higher temperature, which seriously restricts the development and application of the material. The inventors of the present invention have found through continuous research that one or more high entropy metal oxide materials can be synthesized at 300-400°C using specific metal salts as raw materials. The equipment requirements are not high, the process is simple, and it is suitable for large-scale production.
[0036] Specifically, the present invention provides a method for preparing a high entropy metal oxide, which comprises the steps of adding a plurality of metal salts into a solvent containing a template and mixing them into a uniform sol, and sequentially aging, drying and calcining the sol to obtain the high entropy metal oxide;
[0037] The metal salt is selected from at least five of cerium salts, zirconium salts, hafnium salts, tantalum salts, niobium salts, titanium salts, vanadium salts, molybdenum salts, tungsten salts, copper salts, zinc salts and aluminum salts;
[0038] The template agent is selected from one of polyether P123, branched polyethyleneimine (BPEI), xanthan gum, ε-polylysine, pluronic F-127 and polyvinyl pyrrolidone (PVP).
[0039] It should be understood that among the metal salts mentioned above, technicians in this field can select five or more types for use in the preparation method described in the present invention according to actual needs, such as cerium salts, zirconium salts, niobium salts, tantalum salts, and hafnium salts; or cerium salts, copper salts, zinc salts, zirconium salts, and aluminum salts.
[0040] It should be understood that the above-mentioned templates can be selected by those skilled in the art according to actual needs and applied to the preparation method of the present invention, such as polyether P123.
[0041] In one or more embodiments, the cerium salt is selected from one of cerium oxalate, cerium chloride, cerium nitrate, ammonium cerium nitrate, cerium trifluoromethanesulfonate and cerium stearate; the zirconium salt is selected from one of zirconium acetylacetonate, zirconium oxychloride, zirconium chloride and zirconium nitrate; the hafnium salt is selected from one of hafnium tetrachloride, hafnium n-butoxide and hafnium oxychloride hydrate; the tantalum salt is selected from one of tantalum chloride, tantalum ethoxide, tantalum tetraethanol acetylacetonate and tantalum isopropoxide; the niobium salt is selected from one of niobium pentachloride, ammonium hexafluoroniobate and niobium n-butoxide; the titanium salt is selected from one of titanium tetrachloride, hexafluoro One of titanic acid and titanium acetylacetonate; the vanadium salt is selected from one of vanadium trichloride, vanadium acetylacetonate and ammonium metavanadate; the molybdenum salt is selected from one of molybdenum chloride, ammonium molybdate and molybdenum acetylacetonate; the tungsten salt is selected from one of ammonium tungstate, tungsten hexachloride and tungsten isopropoxide; the copper salt is selected from one of copper nitrate, copper oxalate, copper stearate, copper methanesulfonate and copper chloride; the zinc salt is selected from one of zinc chloride, zinc stearate, zinc oxalate and zinc nitrate; the aluminum salt is selected from one of aluminum nitrate, aluminum acetate, aluminum stearate, aluminum acetylacetonate and aluminum chloride.
[0042] It should be understood that the specific metal salts mentioned above can be selected or combined by those skilled in the art according to actual needs, such as cerium nitrate, zirconium oxychloride, niobium chloride, tantalum chloride and hafnium chloride; or cerium nitrate, copper nitrate, zinc nitrate, zirconium oxychloride and aluminum nitrate.
[0043] In one or more embodiments, the molar mass of the plurality of metal salts is 0.5 mmol to 10 mol; and the molar mass of the template is 25 to 40 mmol.
[0044] It should be understood that the molar mass of the metal salts described in the present invention or the molar ratio between different metal salts is not limited. Those skilled in the art can adjust the specific usage of each metal salt according to actual needs, and the adjustment of each metal salt within a certain range will not have a substantial impact on the preparation method of the present invention or the final high entropy metal oxide.
[0045] In one or more embodiments, the aging step is: stirring the homogeneous sol for 1 to 2 hours, and then aging it for 40 to 50 hours at a temperature of 35 to 45° C. and a humidity of 45 to 55%.
[0046] In one or more embodiments, the drying temperature is 90 to 110° C., and the drying time is 20 to 30 hours.
[0047] In one or more embodiments, the calcination step is: heating the dried product to 300° C. to 400° C. at a heating rate of 1° C. per minute in air, and then calcining for 3 to 5 hours.
[0048] In one or more embodiments, the metal salt includes 5 mmol cerium nitrate, 2 mmol zirconium oxychloride, 1.5 mmol niobium chloride, 1 mmol tantalum chloride and 0.5 mol hafnium chloride; the template is 35 mmol polyether P123; the obtained high entropy metal oxide is Ce 0.5 Zr 0.2 Nb 0.15 Ta 0.1 Hf 0.05 O x , where X=1-3.
[0049] In one or more embodiments, the metal salt includes 5 mmol cerium nitrate, 2 mmol copper nitrate, 1 mmol zinc nitrate, 0.5 mmol zirconium oxychloride and 0.5 mmol aluminum nitrate; the template is 30 mmol pluronic F-127; the obtained high entropy metal oxide is Ce 0.5 Cu 0.2 Zn 0.1 Zr 0.05 Al 0.05 O x , where X=1-3.
[0050] In one or more embodiments, the metal salt includes 4 mmol copper nitrate, 2 mmol molybdenum chloride, 2 mmol ammonium metavanadate, 1 mmol tungsten hexachloride, 0.5 mmol aluminum chloride and 0.5 mmol titanium chloride; the template is 40 mmol PVP; the obtained high entropy metal oxide is Cu 0.4 Mo 0.2 V 0.2 W 0.1 Al 0.05 Ti 0.05 O x , where X=1-3.
[0051] The high entropy metal oxide prepared by the method described above in the present invention not only has a uniform morphology, but also has a composition of multiple elements so that it has a high specific surface area and a controllable local electronic structure, thereby having better catalytic performance; and it can effectively catalyze the oxidation of halogen ions in the presence of H2O2 oxidant, thereby generating hypohalous acid with strong antibacterial activity, thereby preventing the attachment of marine organisms. Therefore, the high entropy metal oxide described in the present invention exhibits excellent anti-marine biofouling performance and has obvious advantages in the field of preparing anti-marine biofouling materials. In addition, the high entropy metal oxide can efficiently catalyze the generation of hydrogen peroxide in aqueous solution under light conditions, which not only enhances its antibacterial properties, but also provides new application prospects for photocatalytic systems. Therefore, the high entropy metal oxide described in the present invention has excellent anti-marine biofouling performance, and also shows significant advantages in photocatalytic production of hydrogen peroxide.
[0052] The high entropy metal oxide material of the present invention has not been reported in the field of marine antifouling. It innovatively introduces the concept of high entropy into the development of high-performance nanozymes, combining advanced high entropy metal oxides with haloperoxidase-like active sites. The high adjustability and flexibility of this material in multidimensional composition space provide an effective strategy for building efficient catalysts to meet key challenges. In addition, the high entropy metal oxide material of the present invention can efficiently catalyze the generation of hydrogen peroxide in aqueous solution under illumination conditions. This feature not only enhances its antifouling performance, but also opens up a new path for its application in the field of photocatalysis. Compared with other antifouling coatings, the high entropy metal oxide of the present invention will not release heavy metal ions into the ocean during use, which can avoid the destruction of the marine ecosystem. The material is non-radioactive, has the advantages of environmental protection, non-toxicity, low cost, and easy preparation. It will not cause adverse effects on non-target organisms and the environment, and is an ideal environmentally friendly marine antifouling material.
[0053] The high entropy metal oxide material of the present invention has the above-mentioned excellent properties, and therefore can be applied in the field of marine engineering. Preferably, the high entropy oxide can be used to prepare anti-marine biofouling materials.
[0054] It should be understood that the inventors have only tested some of the properties of the high entropy metal oxide obtained by the preparation method of the present invention, which does not mean that the high entropy metal oxide of the present invention has poor or inferior performance in other aspects. In particular, the core creative content of the present invention includes but is not limited to the following points:
[0055] 1. Application of high entropy metal oxide materials in marine antifouling;
[0056] 2. The material simulates the catalytic activity of haloperoxidase;
[0057] 3. The ability of this material to catalyze the production of hydrogen peroxide under light conditions, and its potential application in improving antifouling effects and promoting environmentally friendly energy production.
[0058] Example
[0059] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0060] Before further describing the specific embodiments of the present invention, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terms used in the examples of the present invention are for describing specific embodiments rather than for limiting the scope of protection of the present invention.
[0061] When the embodiment gives a numerical range, it should be understood that, unless otherwise specified in the present invention, the two endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art to which the present invention belongs.
[0062] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased through regular channels.
[0063] The examples involve the addition amounts, contents and concentrations of various substances, wherein the percentages described therein, unless otherwise specified, are all by mass percentages.
[0064] Example 1: Ce 0.5 Zr 0.2 Nb 0.15 Ta 0.1 Hf 0.05 O x Preparation
[0065] A method for preparing a high entropy metal oxide comprises the following steps: first weighing 35 mmol of polyether P123 and dissolving it in 40 ml of anhydrous ethanol, and then respectively adding 5 mmol of cerium nitrate, 2 mmol of zirconium oxychloride, 1.5 mmol of niobium chloride, 1 mmol of tantalum chloride and 0.5 mol of hafnium chloride. The above system is mixed into a uniform sol, stirred at room temperature for two hours, placed in an oven at 40°C, and aged for 48 hours under 50% humidity conditions. The obtained gel product is dried at 100°C for 24 hours, and then calcined at 400°C in air at a heating rate of 1°C per minute for 4 hours to obtain a high entropy metal oxide Ce. 0.5 Zr 0.2 Nb 0.15 Ta 0.1 Hf 0.05 O x , where X=1-3.
[0066] Example 2: Ce 0.5 Cu 0.2 Zn 0.1 Zr 0.05 Al 0.05 O x Preparation
[0067] A method for preparing a high entropy metal oxide comprises the following steps: first weighing 30 mmol of pluronic F-127 and dissolving it in 40 ml of anhydrous ethanol, and then respectively adding 5 mmol of cerium nitrate, 2 mmol of copper nitrate, 1 mmol of zinc nitrate, 0.5 mmol of zirconium oxychloride and 0.5 mmol of aluminum nitrate. The above system is mixed into a uniform sol, stirred at room temperature for one hour, placed in an oven at 35°C, and aged for 50 hours under a humidity condition of 45%. The obtained gel product is dried at 110°C for 20 hours, and then calcined at 300°C in air at a heating rate of 1°C per minute for 5 hours to obtain a high entropy metal oxide Ce. 0.5 Cu 0.2 Zn 0.1 Zr 0.05 Al 0.05 O x , where X=1-3.
[0068] Example 3: Cu 0.4 Mo 0.2 V 0.2 W 0.1 Al 0.05 Ti 0.05 O x Preparation
[0069] A method for preparing a high entropy metal oxide comprises the following steps: first weigh 30 mmol of pluronic F-127 and dissolve it in 40 ml of anhydrous ethanol, then respectively add 4 mmol of copper nitrate, 2 mmol of molybdenum chloride, 2 mmol of ammonium metavanadate, 1 mmol of tungsten hexachloride, 0.5 mmol of aluminum chloride and 0.5 mmol of titanium chloride. The above system is mixed into a uniform sol, stirred at room temperature for 1.5 hours, placed in an oven at 45°C, and aged for 40 hours at a humidity of 55%. After drying the obtained gel product at 90°C for 30 hours, calcined at 350°C in air at a heating rate of 1°C per minute for 3 hours to obtain a high entropy metal oxide Cu 0.4 Mo 0.2 V 0.2 W 0.1 Al 0.05 Ti 0.05 O x , where X=1-3.
[0070] Test example 1: Structural analysis of high entropy metal oxides
[0071] (1) The high entropy metal oxide prepared by the method described in Example 1 was tested using a scanning electron microscope. Figure 1The results show that the material prepared by the above experiment has a typical porous configuration, with a length of about 2 μm, uniform morphology, and high dispersion, which is convenient for further preparation of uniform antifouling film materials as coatings.
[0072] (2) The high entropy metal oxide prepared by the method described in Example 1 was tested by X-ray diffraction (XRD). Figure 2 The results show that the sample prepared by the above experiment has multiple obvious diffraction peaks, indicating that the high entropy metal oxide prepared in Example 1 has a polycrystalline structure and good crystallinity.
[0073] Test Example 2: Catalytic Behavior of High Entropy Metal Oxides in H2O2 / Br- Environment
[0074] The ultraviolet-visible absorption spectrometer was used to study the high entropy metal oxides prepared by the methods described in Examples 1 and 2 in H2O2 / Br - The catalytic behavior of high entropy metal oxides (50 μg mL -1 ) in H2O2 / Br - (490μM / 25mM) environment, using phenol red (50μM) as a colorimetric agent, the reaction solution was scanned by a time-dependent UV-visible spectrophotometer curve. The results are shown in Figure 3 and Figure 4 shown.
[0075] from Figure 3 The results show that: as time goes by, the ultraviolet absorbance of the reaction solution at 430nm (absorption peak of phenol red) gradually decreases, while the absorption peak at 590nm (absorption peak of bromophenol blue generated by bromination of phenol red) gradually increases, confirming the continuous generation of hypobromous acid during the catalytic process, and further indicating that the high entropy metal oxide prepared in Example 1 can simulate vanadium haloperoxidase, and can effectively catalyze the oxidation of halogen ions in the presence of H2O2 oxidant to generate hypohalous acid with strong antibacterial activity, which can effectively prevent the attachment of marine microorganisms.
[0076] from Figure 4 The results show that: as time goes by, the ultraviolet absorbance of the reaction solution at 430nm (absorption peak of phenol red) gradually decreases, while the absorption peak at 590nm (absorption peak of bromophenol blue generated by bromination of phenol red) gradually increases, confirming the continuous generation of hypobromous acid during the catalytic process, and further indicating that the high entropy metal oxide prepared in Example 2 can simulate vanadium haloperoxidase, and can effectively catalyze the oxidation of halogen ions in the presence of H2O2 oxidant to generate hypohalous acid with strong antibacterial activity, which can effectively prevent the attachment of marine microorganisms.
[0077] Test Example 3: Catalytic Behavior of High Entropy Metal Oxides on Hydrogen Peroxide Generation under Light Conditions
[0078] The catalytic behavior of the high entropy metal oxides prepared by the methods described in Examples 1 and 2 on the generation of hydrogen peroxide under light conditions was studied using an ultraviolet-visible absorption spectrometer. -1 ) was dissolved in water and the experiment was carried out under light. The generation of hydrogen peroxide was monitored by time-dependent UV-visible spectrophotometer curve scanning. The results are as follows Figure 5 and Figure 6 shown.
[0079] Figure 5 The yield of hydrogen peroxide at different time points is shown, and it can be seen that the yield of hydrogen peroxide increases significantly with the extension of the illumination time. This result shows that the high entropy metal oxide prepared in Example 1 can efficiently catalyze the generation of hydrogen peroxide under illumination conditions, thereby providing experimental evidence and potential application value for its application in the field of photocatalysis.
[0080] Figure 6 The yield of hydrogen peroxide at different time points is shown, and it can be seen that the yield of hydrogen peroxide increases significantly with the extension of the illumination time. This result shows that the high entropy metal oxide prepared in Example 2 can efficiently catalyze the generation of hydrogen peroxide under illumination conditions, thereby providing experimental evidence and potential application value for its application in the field of photocatalysis.
[0081] Test Example 4: Testing of High Entropy Metal Oxides in Marine Anti-Biofouling
[0082] The high entropy metal oxides (1.2 g) prepared in Examples 1, 2 and 3 were respectively mixed with commercial marine coating AkzoNobel toplacwhite 001 (24 g) and coated on stainless steel plates. An equal amount of commercial marine coating (24 g) was coated on stainless steel plates as a control and suspended in a real marine environment for 90 days.
[0083] like Figure 7 As shown, (b) is a photo of the high entropy metal oxide prepared in Example 1 mixed with commercial ship coating and coated on a stainless steel plate and then hung in a real marine environment for 90 days, and (a) is a photo of the commercial ship coating coated on stainless steel and hung in a real marine environment for 90 days. By comparing the results, it is found that compared with the blank control stainless steel plate (a), the substrate (b) treated with the high entropy metal oxide coating has greatly reduced biofouling, which fully proves that the high entropy metal oxide described in the present invention has excellent anti-biofouling ability.
[0084] like Figure 8As shown, (d) is a photo of the high entropy metal oxide prepared in Example 2 mixed with commercial ship coating and then coated on a stainless steel plate and hung in a real marine environment for 90 days, and (c) is a photo of the commercial ship coating coated on stainless steel and hung in a real marine environment for 90 days. By comparing the results, it is found that compared with the blank control stainless steel plate (c), the substrate (d) treated with the high entropy metal oxide coating has greatly reduced biofouling, which fully proves that the high entropy metal oxide described in the present invention has excellent anti-biofouling ability.
[0085] like Fig. 9 As shown, (f) is a photo of the high entropy metal oxide prepared in Example 3 mixed with commercial ship coating and then coated on a stainless steel plate and hung in a real marine environment for 90 days, and (e) is a photo of the commercial ship coating coated on stainless steel and hung in a real marine environment for 90 days. By comparing the results, it is found that compared with the blank control stainless steel plate (e), the substrate (f) treated with the high entropy metal oxide coating has greatly reduced biofouling, which fully proves that the high entropy metal oxide described in the present invention has excellent anti-biofouling ability.
[0086] The above is only an implementation method of the present invention. It should be pointed out that, for ordinary technicians in this field, changes can be made without departing from the concept of the present invention, and these all fall within the scope of protection of the present invention.
Claims
1. A method for preparing a high entropy metal oxide, characterized in that: The preparation method comprises the steps of adding a plurality of metal salts into a solvent containing a template and mixing them into a uniform sol, and sequentially aging, drying and calcining the sol to obtain the high entropy metal oxide; The metal salt is selected from at least five of cerium salts, zirconium salts, hafnium salts, tantalum salts, niobium salts, titanium salts, vanadium salts, molybdenum salts, tungsten salts, copper salts, zinc salts and aluminum salts; The template agent is selected from one of polyether P123, branched polyethyleneimine, xanthan gum, ε-polylysine, pluronic F-127 and polyvinyl pyrrolidone.
2. The preparation method according to claim 1, characterized in that The cerium salt is selected from one of cerium oxalate, cerium chloride, cerium nitrate, ammonium cerium nitrate, cerium trifluoromethanesulfonate and cerium stearate; the zirconium salt is selected from one of zirconium acetylacetonate, zirconium oxychloride, zirconium chloride and zirconium nitrate; the hafnium salt is selected from one of hafnium tetrachloride, hafnium n-butoxide and hafnium oxychloride hydrate; the tantalum salt is selected from one of tantalum chloride, tantalum ethoxide, tantalum tetraethanol acetylacetonate and tantalum isopropoxide; the niobium salt is selected from one of niobium pentachloride, ammonium hexafluoroniobate and niobium n-butoxide; the titanium salt is selected from one of titanium tetrachloride, hexafluorotitanic acid and acetylacetone. The vanadium salt is selected from one of vanadium trichloride, vanadium acetylacetonate and ammonium metavanadate; the molybdenum salt is selected from one of molybdenum chloride, ammonium molybdate and molybdenum acetylacetonate; the tungsten salt is selected from one of ammonium tungstate, tungsten hexachloride and tungsten isopropoxide; the copper salt is selected from one of copper nitrate, copper oxalate, copper stearate, copper methanesulfonate and copper chloride; the zinc salt is selected from one of zinc chloride, zinc stearate, zinc oxalate and zinc nitrate; the aluminum salt is selected from one of aluminum nitrate, aluminum acetate, aluminum stearate, aluminum acetylacetonate and aluminum chloride.
3. The preparation method according to claim 1, characterized in that: The molar mass of the multiple metal salts is 0.5 mmol to 10 mol; the molar mass of the template is 25 to 40 mmol.
4. The preparation method according to claim 1, characterized in that: The aging step is: stirring the homogeneous sol for 1 to 2 hours, and then aging it for 40 to 50 hours at a temperature of 35 to 45° C. and a humidity of 45 to 55%.
5. The preparation method according to claim 1, characterized in that: The drying temperature is 90-110° C. and the drying time is 20-30 hours.
6. The preparation method according to claim 1, characterized in that: The calcination step is: heating the dried product to 300°C to 400°C at a heating rate of 1°C per minute in air, and then calcining for 3 to 5 hours.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The metal salt includes 5mmol cerium nitrate, 2mmol zirconium oxychloride, 1.5mmol niobium chloride, 1mmol tantalum chloride and 0.5mol hafnium chloride; the template is 35mmol polyether P123; the obtained high entropy metal oxide is Ce 0.5 Zr 0.2 Nb 0.15 Ta 0.1 Hf 0.05 O x , where X=1-3.
8. The preparation method according to any one of claims 1 to 6, characterized in that: The metal salt includes 5mmol cerium nitrate, 2mmol copper nitrate, 1mmol zinc nitrate, 0.5mmol zirconium oxychloride and 0.5mmol aluminum nitrate; the template is 30mmol pluronic F-127; the obtained high entropy metal oxide is Ce 0.5 Cu 0.2 Zn 0.1 Zr 0.05 Al 0.05 O x , where X=1-3.
9. The preparation method according to any one of claims 1 to 6, characterized in that: The metal salt includes 4mmol copper nitrate, 2mmol molybdenum chloride, 2mmol ammonium metavanadate, 1mmol tungsten hexachloride, 0.5mmol aluminum chloride and 0.5mmol titanium chloride; the template agent is 40mmol polyvinyl pyrrolidone; the obtained high entropy metal oxide is Cu 0.4 Mo 0.2 V 0.2 W 0.1 Al 0.05 Ti 0.05 O x , where X=1-3.
10. Application of the high entropy oxide obtained by the preparation method according to any one of claims 1 to 9 in the field of marine engineering. Preferably, the application is to use the high entropy oxide for preparing anti-marine biofouling materials.
Citation Information
Patent Citations
High-entropy oxide catalyst with high specific surface area and preparation method and application thereof
CN116037149A
Cited By
High-entropy sub-nano enzyme as well as preparation method and application thereof
CN120392677A